Performance evaluation of thread pool configurations in the run-time systems of integration platforms - Freire, D. L.; Mazzonetto, A.; Frantz, R. Z.; Roos-Frantz, F.; Sawicki, S.; Basto-Fernandes, V. (International Journal of Business Process Integration and Management, 2021)
Companies’ software ecosystem – composed of local applications and cloud computing services – is made up by the connection of integration platforms and applications. Run-time systems are arguably the most considerable components for integration platforms performance. Our literature review has identified that most integration run-time systems adopt a global pool as configuration for threads. However, it is possible to configure local thread pools to increase the performance of run-time systems. This article brings a comparison between two configurations of thread pools simulating the execution of a real integration problem. Results show that the execution performance through the local pool configuration exceeds the performance through the global pool in high workload scenarios. These results were reviewed by rigorous statistical analysis.